Pelaksanaan Badan Permusyawaratan Desa Dalam Pembentukan Peraturan Desa Umauta Kecamatan Bola Kabupaten Sikka - Teddy, Yosef; Stefanus, Kotan Y; Ratu Udju, Hernimus (Artemis Law Journal, 2023)
The village consultative body is one of the elements in the village government, which is expected to help realize the formation and implementation of village regulations in accordance with the aspirations of the community. However, in carrying out its duties and authorities, the village consultative bady in Umauta village has not been optimal submitting draft village regulation, poor coordination between members of the village consultative body and the village government in the formation of village regulations, education level of village government officials. Low and inadequate facilities and infrastructure. This study usesan empiricial juridical approach, namely the methods and procedures used to solve problems, this research first examines secondary data, then proceeds with conducting research on primary data in the field and the sample from this study includes the village head and Umauta village apparatus, namely the chairman and members of the village consultative body in community leaders of Umauta village. The results of the study indicate that the Umauta village consultative body in carrying out its duties has not succeeded in establishing village regulations, from the results of this study it can be concluded that the Umauta village consultative body and the Umauta village government apparatus require special upgrading or training so that they can carry out their duties and powers in accordance with law Number 6 of 2014 concerning villages.